Evaluasi dan Pengukuran Keberhasilan Usaha Pendidikan: Penelitian - Takdirmin; Rosliah; Hardianto; Husnul Khatimah; Nurul Amadyah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Education is the main foundation of a nation's development, and the quality of education is an important indicator of a country's progress. However, many educational institutions still face challenges in improving the quality of their services and the effectiveness of their programs. This research aims to discuss the evaluation and measurement of the success of educational endeavors, focusing on the definition of evaluation, factors that influence success, and relevant measurement indicators. The research method used is a descriptive qualitative approach, by collecting data from various sources such as journals, books and interviews. The results show that the success of an educational endeavor is not only measured by academic results, but also by student satisfaction, parental loyalty, and the institution's image in the community. In addition, factors such as opportunity utilization, careful planning and competent human resource management greatly influence the success of education. The conclusion of this study emphasizes the importance of systematic evaluation and the use of clear indicators in assessing the success of educational ventures. Thus, educational institutions are expected to formulate more effective strategies to improve the quality of their education and their competitiveness in an increasingly competitive global era.